IMPLEMENTATION OF DIGITAL ASSIGNMENTS TO IMPROVE HIGH ORDER THINKING SKILLS (HOTs) ABILITY OF SENIOR HIGH SCHOOL STUDENTS IN THE CONCEPT OF NEWTON'S LAW - Iwan Permana Suwarna; Fatimah Fatimah (EDUSAINS, 2018)
IMPLEMENTASI PENUGASAN DIGITAL UNTUK MENINGKATKAN HIGH ORDER THINKING SKILLS (HOTs) PADA  KEMAMPUAN SISWA MENENGAH ATAS  DALAM KONSEP HUKUM NEWTON AbstractThe research was conducted in SMAN 7 South Tangerang in the even semester of academic year 2017/2018 with the aim to know the improvement of HOTs of senior high school students after using digital assignment. The research method used is quasi experiment with design of non-equivalent control group. The numbers of respondents in this research are 80 students. Instruments used in the form of a high order thinking ability, instrument that has been tested for its validity and reliability. The numbers of questions in use as many as 23 questions. Conclusion: Digital assignments can improve students' HOTs. All classes that use digital assignments have a higher order of HOTs than a print-based (conventional) class. Use of the Digital assignment method can be: teacher's main consideration in training and improving students' HOTs; and tools for teacher correcting student assignment results; Digital assignment can be applied to the students to deepen the material or concept, to train the national exam questions in digital form.AbstrakPenelitian ini dilakukan di SMAN 7 Tangerang Selatan pada semester genap tahun akademik 2017/2018 dengan tujuan untuk mengetahui peningkatan High Order Thinking Skills (HOTs) siswa SMA setelah menggunakan tugas digital. Metode penelitian yang digunakan adalah quasi eksperimen dengan desain kelompok kontrol tidak setara. Jumlah responden dalam penelitian ini adalah 80 siswa. Instrumen yang digunakan berupa kemampuan HOTs, instrumen yang telah diuji validitas dan reliabilitasnya. Jumlah pertanyaan yang digunakan sebanyak 23 pertanyaan. Kesimpulan: Tugas digital dapat meningkatkan HOTs siswa. Semua kelas yang menggunakan tugas digital memiliki urutan HOTs lebih tinggi daripada kelas berbasis cetak (konvensional). Penggunaan metode penugasan Digital dapat berupa: pertimbangan utama guru dalam melatih dan meningkatkan HOTs siswa; dan alat untuk mengoreksi hasil tugas siswa; Tugas digital dapat diterapkan pada siswa untuk memperdalam materi atau konsep, untuk melatih soal-soal ujian nasional dalam bentuk digital.